Five new species of Stenochrus (Schizomida: Hubbardiidae) from Oaxaca, Mexico - Monjaraz-Ruedas, Rodrigo; Francke, Oscar F. (Zootaxa, 2018)
The North American genus Stenochrus is represented by 22 species distributed mainly in Mexico, Central America and the U.S.A.; the genus was erected originally to place the species Stenochrus portoricensis and was characterized by the presence of lateral lobes reduced on female spermathecae, male flagellum without important dorsal relief, pedipalps without distinctive armature and without posterodorsal process on segment XII. Here we describe five new species from the Mexican state of Oaxaca; we discuss the presence of dimorphic males in the genus. With this contribution the genus Stenochrus reaches 27 species, becoming the second most diverse genus of schizomids in the New World.